Dendrimers in vaccine delivery: Recent progress and advances. (January 2022) - Chowdhury, Silvia; Toth, Istvan; Stephenson, Rachel J.
Abstract: Dendrimers are well-defined, highly branched, multivalent and monodisperse molecules which host a range of attractive, yet functional, chemical and biological characteristics. A dendrimers accessible surface groups enable coupling to different functional moieties ( e.g., antibodies, peptides, proteins, etc), which is further assisted by the dendrimers tailored size and surface charge. This adaptability allows for the preparation of molecularly precise vaccines with highly specific and predictable properties, and in conjunction with a dendrimers immune stimulating (adjuvanting) property, makes dendrimers attractive substrates for biomedical applications, including vaccines. This review highlights the structural and synthetic evolution of dendrimers throughout history, detailing the dendrimers role as both an adjuvant and carrier system for vaccine antigens, in addition to reviewing the development of commercially available vaccines for use in humans.